Kompetencje językowe dzieci z głuchotą prelingwalną zaimplantowanych do drugiego roku życia - Magierska-Krzysztoń, Magdalena; Olempska-Wysocka, Magdalena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Early implantation and hearing and speech rehabilitation provide much wider opportunities to develop linguistic and communication skills for children with hearing impairment. The article presents own research, the aim of which was to determine the level of language competence of children with prelingual hearing deafness, which were implanted with a cochlear implant until the second year of life. The study involved a group of 169 children with prelingual hearing deafness. The tests used 6 Ling’s sounds, the MAIS scale, the MUSS scale and the TAPS test.